Wallerian Degeneration, Wld(S), and Nmnat - Coleman, Michael P. (Annu Rev Neurosci, 2010)
Traditionally, researchers have believed that axons are highly dependent on their cell bodies for long-term survival. However, recent studies point to the existence of axon-autonomous mechanism(s) that regulate rapid axon degeneration after axotomy. Here, we review the cellular and molecular events that underlie this process, termed Wallerian degeneration. We describe the biphasic nature of axon degeneration after axotomy and our current understanding of how Wld(S)—an extraordinary protein formed by fusing a Ube4b sequence to Nmnat1—acts to protect severed axons. Interestingly, the neuroprotective effects of Wld(S) span all species tested, which suggests that there is an ancient, Wld(S)-sensitive axon destruction program. Recent studies with Wld(S) also reveal that Wallerian degeneration is genetically related to several dying back axonopathies, thus arguing that Wallerian degeneration can serve as a useful model to understand, and potentially treat, axon degeneration in diverse traumatic or disease contexts.